The Effect of Coach Leadership Style on Athlete’s Performance of Athletics Club of Addis Ababa - Getu Yemiru, Zemikael (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2022)
The purpose of this study is to explore the effect of coaches-leadership styles on athletes’ performance. A sample of athlete participants (n=55) from Defense athletics clubs of Addis Ababa was used using the convenience sampling technique. The study used a mixed-methods study design, integrating quantitative and qualitative approaches, a five-point Likert scale; an RLSS questionnaire was used to determine the impact of coach-leadership style on athletes’ performance. SPSS software version 24 was used in analyzing the athlete’s responses to questionnaires. Demographic analysis, descriptive analysis, and regression analysis were presented. Descriptive statistics show that the most significant value associated with athletes’ performance is the democratic leadership style followed by the social consideration leadership style and positive feedback leadership style. Democratic leadership style has the highest mean value corresponding to 3.05 and standard deviation value of 0.37, social consideration leadership style scores the second highest mean value corresponding to 3.03 and standard deviation value of 0.47, and positive feedback mean value 3.02 and standard deviation of 0.39, and social support mean value 3.01 and standard deviation 0.47and training and instruction mean value 3.00 and standard deviation 0.48 and autocratic leadership style has the lowest mean value corresponding to 2.93 and standard deviation value of 0.54 indicating that autocratic leadership style is poorly correlated with athletes performance. Regression coefficient analysis shows that there is a significant and positive impact of training and instruction leadership styles on athletes’ performance. The social support style beta coefficient value is 0.23 with a significant value of 0.958 which is higher than 0.05, hence social support style was found to have not a statistically significant impact on athlete’s performance. Recommendation shows the use of more demographic factors to determine their influence on athletes’ performances.